Hitaveita Reykjavikur and the Nesjavellir Geothermal Co-Generation Power Plant - Lund, John W. (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 1996)
When Ingólfur Arnarson sighted land on the voyage which would make him the first settler in Iceland, he threw the pillars of his high seat overboard and relied on the gods to direct him to where he should settle. His slaves found them washed ashore in a bay where "smoke" rose out of the ground. Therefore, they call it Reykjavik, "Smoky Bay." But the smoke after which Iceland's capital is named was not the result of a fire, but was rather steam rising from hot springs